Effect of weight reduction on glycated haemoglobin in weight loss trials in patients with type 2 diabetes. Issue 9 (22nd May 2017) - Gummesson, Anders; Nyman, Elisabeth; Knutsson, Mikael; Karpefors, Martin
Abstract : Aim: To quantify the effect of weight loss on glycated haemoglobin (HbA1c) at group level, based on data from published weight loss trials in overweight and obese patients with type 2 diabetes (T2D). Methods: A systematic literature search in MEDLINE, EMBASE and Cochrane CENTRAL (January 1990 through December 2012) was conducted to identify prospective trials of energy‐reduced diets, obesity drugs or bariatric surgery in adult, overweight and obese patients with T2D. Based on clinical data with follow‐up from 3 to 24 months, a linear model was developed to describe the effect of weight reduction on HbA1c. Results: The literature search identified 58 eligible articles consisting of 124 treatment groups and 17 204 subjects, yielding a total of 250 data points with concurrent mean changes from baseline in weight and HbA1c. The model‐based analyses indicated a linear relationship between weight loss and HbA1c reduction, with an estimated mean HbA1c reduction of 0.1 percentage points for each 1 kg of reduced body weight for the overall population. Baseline HbA1c was a significant covariate for the relationship between weight loss and HbA1c: high HbA1c at baseline was associated with a greater reduction in HbA1c for the same degree of weight loss. The collected trial data also indicated weight‐loss‐dependent reductions in antidiabetic medication. Conclusions: At group level, weight loss in obese and overweight patients with T2D was consistently accompanied by HbA1c reduction in a dose‐dependent manner. The model developed in the present study estimates that for each kg of mean weight loss, there is a mean HbA1c reduction of 0.1 percentage points. HbA1c‐lowering is greater in populations with poor glycaemic control than in well controlled populations with the same degree of weight loss. This summary of data from previous trials regarding the effect of weight reduction on HbA1c may be used to support the design and interpretation of future studies that aim to demonstrate the efficacy of weight loss interventions for T2D treatment.